Magnitogorsk, de jeugd van de hoogovens . Magnitogorsk: Forging the New Man - Smit, Pieter Jan (Viewpoint Productions, 1996)
Verzio FF Duration: 01:00:00 In the early thirties, the bare steppes of the Urals were transformed at breakneck speed into a blast-furnace complex and a city was erected out of nothing. Magnitogorsk was a model project to demonstrate the energy with which the first five-year plan of the communist state-controlled economy was put into operation. In 1932, Joris Ivens was invited to make a film about the building of the Soviet Union. He chose Magnitogorsk as an example of how the new world and the new man were to be forged, and the resulting film, Song of the heroes, encapsulates the prevailing ideology of the period. Joris Ivens lauded the enthusiasm with which the blast-furnace project was brought to fruition. Pieter Jan Smit's documentary sets out to find those who built and resided in the city of steel and to talk to them about their ideals yesterday and today. Magnitogorsk shows us what became of the heroes of Ivens' film.